2006
DOI: 10.1007/s11267-005-9024-z
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Phytoremediation of Pahs Contaminated Soils Following a Bioremediation Treatment

Abstract: Phytoremediation of pollutants in soils is an emerging technology, using different soilplant interaction properties. For organic pollutants, such as polycyclic aromatic hydrocarbons (PAHs), phytodegradation seems to be the most promising approach. It occurs mostly through an increase of the microbial activity in the plant rhizosphere, allowing the degradation of organic substances, a source of carbon for soil microbes. Despite a large amount of available data in the literature concerning laboratory and short t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
4
13
0
1
Order By: Relevance
“…In our study, the AHs contents in the second year were higher than the initial values in the first three treatments. Similar results were also observed in some other studies (Banks et al 2003;Denys et al 2006). We thought that the increase of AHs in this study was probably due to the freeze-thaw process which increased the release of sequestrated AHs, however, this required further studies for detailed explanations.…”
Section: Resultssupporting
confidence: 92%
“…In our study, the AHs contents in the second year were higher than the initial values in the first three treatments. Similar results were also observed in some other studies (Banks et al 2003;Denys et al 2006). We thought that the increase of AHs in this study was probably due to the freeze-thaw process which increased the release of sequestrated AHs, however, this required further studies for detailed explanations.…”
Section: Resultssupporting
confidence: 92%
“…This suggests that planting alfalfa and tall fescue in mixture played an important role in the remediation of the PAHcontaminated soil. This result confirmed the findings from Denys (2006) who found a decrease in soil total PAHs of 25% in a mixture of herbaceous species grown in PAHcontaminated soil in the field. Although the present study shows an overall improvement in dissipation of total PAHs in intercropped treating, this is primarily due to a significantly enhanced dissipation of 4-ring PAHs in A/T plots compared with T plots.…”
Section: Discussionsupporting
confidence: 91%
“…Plant PAH concentrations were thus the highest during the first season and lowest during the third season being however in the same order of magnitude as that of the control plants (not shown). Parallel determinations of PAH concentrations in the plants and PAH degradation rates in the soil indicated that the degradation of PAH (mostly 2-4 rings: naphthalene, phenanthrene, dibenzothiophene, pyrene, fluoranthene and chrysene) was due to rhizospheric bacteria, and that plants decisively improved their growth and working conditions, as already shown by other studies (Nedunuri et al 2000;Huang et al 2005;Denys et al 2006;Liste and Prutz 2006;Palmroth et al 2006;Rezek et al 2008; Gaskin and Bentham 2010). In contrast, the capacity of plant roots to take up PAH from soil appears to be limited (Gao and Ling 2006;Lin et al 2007;Gao and Collins 2009;Xu et al 2009).…”
supporting
confidence: 75%
“…Similar technologies of ecological engineering or ecoremediation can be used for revegetating degraded land (like quarries, road sides), as well as for removing excessive nutrient loads and cleaning-up wastewater (road runoff, municipal and industrial effluents, surface and seepage water) with soil-plant filters, buffer strips and constructed wetlands (Otto et al 2008;Bulc and Slak 2009;Vymazal 2009;Borin et al 2010). Plants represent a more environmentally compatible and less expensive method to site restoration compared to physico-chemical and engineering techniques, even though the time scale required to reach the fixed end-points can become a limiting factor for such ecoremediation approaches (Denys et al 2006;Komives et al 2009;Mench et al 2009Mench et al , 2010Vangronsveld et al 2009). Plants are already cleaning our environment constantly, everywhere, even if we do not recognise or know it.…”
mentioning
confidence: 99%